PRINCIPLE OF SOCIAL JUSTICE AND EQUALITY IN INHERITANCE - Isroilov Bektosh Erkinovich (Innovate Conferences, 2025)
The article discusses the level of study of such phenomena as succession, tradition and renewal by scholars, the scientific sources created by them, and the need for further study of this problem.
Keywords: succession, tradition, renewal, literary development, continuity, repetition, uniqueness.